2021
DOI: 10.2991/ahsr.k.210115.004
|View full text |Cite
|
Sign up to set email alerts
|

Farmers Knowledge on Pesticide Safety Management in Ponorogo

Abstract: Agricultural activities in PonorogoDistrict are one of the largest contributors to the economy. However, agricultural activities related to pesticide use need attention. Based on the previous research, there were 36.7% of farmers in one of the villages in Ponorogo District were at a very high risk of pesticide contamination. This study aims at analyzing farmers' knowledge of pesticide safety management. This descriptive study involved 57 farmers in village X in Ponorogo. The used instrument was a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The results of other studies on the use of PPE have shown that there is a relationship between the use of PPE and cholinesterase(29). This study is in line with the theory proposed by Rosanti et al(30) that pesticide poisoning may occur due to excessive exposure to pesticides or due to disregard of occupational health and safety procedures and inadequate work equipment. Farmers who do not use at least three PPEs experience cholinesterase abnormalities.…”
supporting
confidence: 92%
“…The results of other studies on the use of PPE have shown that there is a relationship between the use of PPE and cholinesterase(29). This study is in line with the theory proposed by Rosanti et al(30) that pesticide poisoning may occur due to excessive exposure to pesticides or due to disregard of occupational health and safety procedures and inadequate work equipment. Farmers who do not use at least three PPEs experience cholinesterase abnormalities.…”
supporting
confidence: 92%
“…In Cambodia's rice farming communities, stakeholder interactions are essential to preserving conditions and mechanisms for transitioning from pesticide use to sustainable pest control practices [45]. Moreover, collaboration between stakeholders can enhance farmers' perception of pesticide safety by analyzing their knowledge of safe pesticide management [46] and resisting pesticide resistance [47]. Regarding soil management, stakeholder cooperation can integrate environmental capacity based on pesticide risk assessment and provide overall protection of soil quality [48].…”
Section: Literature Reviewmentioning
confidence: 99%